A juice extrator - Shamsudin, Rosnah; Ab Aziz, Norashikin; Buang, Nur Salihah (2014)
The present invention relates to a juice extractor comprising: a hopper (100); a crushing chamber (200) including a crushing mechanism (201) and its motor (203); a filtering chamber (300) including a filtering mechanism (301); a container (303) and a juice outlet (305); a switch (400); and a frame (500) that houses all components of the juice extractor; characterized in that the crushing mechanism (201) further comprising two-level roller-cog pairs (201a), (201b) in which the first roller-cog of the pair (201a) rolls clockwise whereas the second roller-cog of the pair (201b) rolls anti-clockwise wherein the two levels of crushing provides optimal crushing of the fruit pulps thus yields more juices. The extraction of the juice from the fruit is optimized through the crushing mechanism (201) and the centrifugal force of the filtering mechanism (301).